Industrial Shifts, Skills Levels, and the Labor Market for White and Black Males - Bound, John; Holzer, Harry J. (The Review of Economics and Statistics, 1993)
In this paper we estimate the effects of industrial shifts in the 1970s and 1980s on the wages and employment of black and white males. We use micro Census data for 52 MSAs, and estimate effects separately by age and education group. The results show that industrial shifts did reduce demand for blacks and 1essskilled males in 1970s and 1980s. Demand shifts away from manufacturing, in particular, reduced employment and wages for black and white males. While the magnitudes of these effects are fairly small for many groups, they can account for one-third to one-half of the employment decline for less-educated young blacks in the 1970s. These results imply fairly large effects on the earnings of less-skilled males in the 1980s as well.